REALIZATION OF INTERTEXTUALITY IN EDITORIALS OF PRESIDENTIAL ELECTION 2019 - Elsi Revita Hasibuan; Anni Holila Pulungan; Sri Minda Murni (LINGUISTIK TERAPAN, 2021)
ABSTRACTA text can be only interpreted through a background information of other text, and this is where intertextuality emerged, to shape another text. This study investigates the realization of intertextuality in articles of opposite editorials related to Presidential Election 2019. The objectives of the study is to evaluate the ways of the intertextuality realized. This research applied qualitative research design. The data were complex clauses which contained of intertextuality from opposite editorials of four newspapers, namely Kompas, Media Indonesia, Analisa, and Waspada started from January 2nd until April 17th 2019. The data were analyzed by using content analysis technique proposed by Elo and Kyngas (2007). The findings showed that; there were five elements those caused intertextuality realized in opposite editorials, they were; paraphrasing, patchwriting, making implicit meaning, putting contrastive conjunction, and last, image building. Keywords: Intertextuality, Realizations, Editorials, Presidential Election, Content Analysis